2013
DOI: 10.1007/s00726-013-1473-5
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-containing energy drink improves sprint performance during an international rugby sevens competition

Abstract: The aim of this study was to determine the effects of a caffeine-containing energy drink on physical performance during a rugby sevens competition. A second purpose was to investigate the post-competition urinary caffeine concentration derived from the energy drink intake. On two non-consecutive days of a friendly tournament, 16 women from the Spanish National rugby sevens Team (mean age and body mass = 23 ± 2 years and 66 ± 7 kg) ingested 3 mg of caffeine per kg of body mass in the form of an energy drink (Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 28 publications
9
62
1
11
Order By: Relevance
“…However, caffeine metabolism is affected by both estrogen and OCS use [20]; therefore, these results cannot be used to inform female team sports athletes. A caffeine-containing energy drink improved sprint and jump performance in female rugby players before and during a rugby tournament [23] and soccer players during a simulated game [24]. However these studies did not take into account hormonal effects on caffeine metabolism and did not study the effects of caffeine exclusively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, caffeine metabolism is affected by both estrogen and OCS use [20]; therefore, these results cannot be used to inform female team sports athletes. A caffeine-containing energy drink improved sprint and jump performance in female rugby players before and during a rugby tournament [23] and soccer players during a simulated game [24]. However these studies did not take into account hormonal effects on caffeine metabolism and did not study the effects of caffeine exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Eccentric extensor muscle activation pre-jump has been suggested to play a role in CMJ height while knee flexor muscle activation was not involved [34]. Previous research in female soccer players has shown an increase in CMJ height after ingestion of an energy drink containing only 3 mg · kg −1 of caffeine, compared to the same energy drink without caffeine [23]. However, this beverage also contained taurine, L-carnitine and sodium bicarbonate, thus a combinatorial effect cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the effect of caffeine on RPE during team-sports and exercise of an exhaustive or intermittent nature is unclear. Caffeine supplementation failed to influence RPE during a 10-km high-intensity cycling time trial in men (Astorino, Cottrell, Talhami Lozano, AburtoPratt, & Duhon, 2012), an 8.2-km time trial in women (Astorino, Roupoli, & Valdivieso, 2012), in female rugby (Del Coso et al, 2013) and soccer players (Lara et al, 2014), or in males performing a multiple-sprint protocol (Glaister et al, 2008). It is possible that the attenuating effects of caffeine on RPE are subject to the level of exercise intensity or that responses are sport and/or activity-dependent.…”
Section: Caffeine Ingestion Enhances Perceptual Responses During Intementioning
confidence: 97%
“…Similarly, caffeine ingestion (6 mg·kg -1 BM) improved sprint times by 0.5-2.9% during a simulated rugby unionspecific test and resulted in improved passing accuracy compared with a placebo (Stuart et al, 2005). In a randomized, double-blinded, placebo-controlled study, the ingestion of a caffeinated beverage (3 mg·kg -1 BM) by members of the Spanish women's rugby sevens team 60 min before exercise increased power output during a 15-s maximal jump test and increased total distance covered per min and distance covered per min at >3.33 m·s -1 during a friendly international tournament compared with the placebo (Del Coso et al, 2013).…”
Section: Ergogenic Aidsmentioning
confidence: 98%